Novel Identification of Bacterial Epigenetic Regulations Would Benefit From a Better Exploitation of Methylomic Data - Payelleville, Amaury; Brillard, Julien (Frontiers in Microbiology, 2021)
DNA methylation can be part of epigenetic mechanisms, leading to cellular subpopulations with heterogeneous phenotypes. While prokaryotic phenotypic heterogeneity is of critical importance for a successful infection by several major pathogens, the exact mechanisms involved in this phenomenon remain unknown in many cases. Powerful sequencing tools have been developed to allow the detection of the DNA methylated bases at the genome level, and they have recently been extensively applied on numerous bacterial species. Some of these tools are increasingly used for metagenomics analysis but only a limited amount of the available methylomic data is currently being exploited. Because newly developed tools now allow the detection of subpopulations differing in their genome methylation patterns, it is time to emphasize future strategies based on a more extensive use of methylomic data. This will ultimately help to discover new epigenetic gene regulations involved in bacterial phenotypic heterogeneity, including during host-pathogen interactions.